2020
DOI: 10.1021/acs.jpcc.0c04031
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transition in Oxidized Ca2N Electrenes: CaO/CaN 2D Heterostructures

Abstract: Based on first-principles calculations, we show that the oxidation of ultrathin films of Ca 2 N electrides (electrenes) drives a hexagonal → tetragonal structural transition. The groundstate configuration of the oxidized monolayer (ML) and bilayer (BL) systems can be viewed as CaO/CaN and CaO/(CaN) 2 /CaO two-dimensional (2D) heterostructures. In both systems, we found nearly free electron states lying near the vacuum level, and the spatial projection reveals that they are localized above the oxidized CaO surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 81 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…The 2D Ca 2 N and Sr 2 N belong to the electrides, in which the excess electrons occupy the crystal cavities and act as anions [338][339][340][341][342][343][344][345][346][347][348][349][350][351][352][353]. Wang et al reported that the compressive strain can greatly enhance the adsorption interaction between Li and Ca 2 N electride to prevent Li from accumulating on the surface, thereby facilitating Li storage (figure 11(a)) [354].…”
Section: D Ca 2 N and Sr 2 Nmentioning
confidence: 99%
“…The 2D Ca 2 N and Sr 2 N belong to the electrides, in which the excess electrons occupy the crystal cavities and act as anions [338][339][340][341][342][343][344][345][346][347][348][349][350][351][352][353]. Wang et al reported that the compressive strain can greatly enhance the adsorption interaction between Li and Ca 2 N electride to prevent Li from accumulating on the surface, thereby facilitating Li storage (figure 11(a)) [354].…”
Section: D Ca 2 N and Sr 2 Nmentioning
confidence: 99%
“…In recent years, limited studies have been devoted to the synthesis of two-dimensional metallic materials. In recent years, Nair et al succeeded in synthesizing MgO, CuO, and CaO metal oxide monolayers by trapping an aqueous solution of corresponding salt in graphene nanoenclosures [5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%